High Nuclease Activity of Long Persisting Staphylococcus aureus Isolates Within the Airways of Cystic Fibrosis Patients Protects Against NET-Mediated Killing - Herzog, Susann; Dach, Felix; de Buhr, Nicole; Niemann, Silke; Schlagowski, Jannik; Chaves-Moreno, Diego; Neumann, Claudia; Goretzko, Jonas; Schwierzeck, Vera; Mellmann, Alexander; Dübbers, Angelika; Küster, Peter; et al. (Frontiers in Immunology, 2019)
Staphylococcus aureus is one of the first and one of the most prevalent pathogens cultured from the airways of cystic fibrosis (CF) patients, which can persist therefor extended periods. Airway infections in CF patients are characterized by a strong inflammatory response of highly recruited neutrophils. One killing mechanism of neutrophils is the formation of neutrophil extracellular traps (NETs), which capture and eradicate bacteria by extracellular fibers of neutrophil chromatin decorated with antimicrobial granule proteins. S. aureus secretes nuclease, which can degrade NETs. We hypothesized, that S. aureus adapts to the airways of CF patients during persistent infection by escaping from NET-mediated killing via an increase of nuclease activity. Sputum samples of CF patients with chronic S. aureus infection were visualized by confocal microscopy after immuno-fluorescence staining of DNA-histone-1-complexes as a specific marker for NETs, S. aureus bacteria and overall DNA structures. Nuclease activity was analyzed in sequential isogenic long persisting S. aureus isolates from an individual CF patient using a FRET- based nuclease activity assay. NET-killing assays were performed with clinical S. aureus isolates to evaluate killing and bacterial survival depending on nuclease activity. To confirm the role of nuclease during NET-mediated killing, a clinical isolate with low nuclease activity was transformed with a nuclease expression vector (pCM28nuc). Two sputa from a CF patient were subjected to RNA-sequence analysis to evaluate the activity of nuclease in vivo. In sputa, S. aureus was associated to extracellular DNA structures. Nuclease activity in clinical S. aureus isolates increased in a time- and phenotype-dependent manner. NET-mediated killing was significantly higher in S. aureus isolates with low compared to isolates with high nuclease activity. Importantly, transformation of the clinical isolate with low nuclease activity with pCM28nuc conferred protection against NET-mediated killing confirming the beneficial role of nuclease for protection against NETs. Also, nuclease expression in in vivo sputa was high, which underlines the important role of nuclease within the highly inflamed CF airways. In conclusion, our data show that S. aureus adapts to the neutrophil-rich environment of CF airways with increasing nuclease expression most likely to avoid NET-killing during long-term persistence.